The Integral Role of Human Resource Management in Achieving Organizational Goals: A Comprehensive Analysis - Dipoatmodjo, Tenri Sayu Puspitaningsih (Abadi Institute, 2024)
The purpose of this journal article is to define the role of human resources within the context of an organization. The article employs a literature research method. Based on the analysis, it can be inferred that human resource management encompasses three key functions: administrative, operational, and the attainment of overall organizational objectives. These functions encompass activities such as recruitment, human resource development, compensation, occupational health and safety management, as well as industrial relations and labor market management. The primary goal of human resource management is to enhance the contribution of human resources (employees) to the organization. It is evident that the success of an organization in achieving its objectives heavily relies on effective management of its personnel. Therefore, it is crucial to employ sound personnel management practices to ensure that the organization accomplishes its predetermined goals. Human resource managers, along with line managers and subcontractors, play vital roles in the pursuit of human resource management objectives.